Biomed central part of Springer Nature [electronic resource] - Infrastructure Services for Open Access C.I.C. (Community Interest Company). (United Kingdom DOAJ, 2020)
BioMed Central is an independent publishing house committed to providing immediate open access to peer-reviewed biomedical research. BioMed Central contains 184 journals (Dec 1, 2007). Many are citation-tracked and already have Impact Factors.
UPMindanao University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; Biology -- Research; Medicine -- Research; Periodicals -- Open access publishing